2015
DOI: 10.4236/health.2015.71007
|View full text |Cite
|
Sign up to set email alerts
|

Features of Developmental Level of Defense Mechanisms and Adjustment Status of University Students in Japan

Abstract: A person with high-level mental defensive functioning exhibits optimal, effective adaptive states when encountering stressors. This may be an important factor in maintaining a sound campus life. Participants were 47 physically and mentally healthy students (average age 19.0 ± 0.6). We first investigated the developmental level of mental defensive functioning as an indicator of participants' adaptive state at the time of the study. We used the Defensive Functioning Scale proposed in the 4 th edition of the Diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In our previous study, we reported features of developmental level of defense mechanisms and adjustment status of university students in Japan. At that time, we revealed a sex difference in stress management and a unisex positive correlation between physical symptoms and mental symptoms [1]. If we could find such features in this study, it would be helpful for university students to live a mentally and physically healthy campus life.…”
Section: Introductionmentioning
confidence: 52%
“…In our previous study, we reported features of developmental level of defense mechanisms and adjustment status of university students in Japan. At that time, we revealed a sex difference in stress management and a unisex positive correlation between physical symptoms and mental symptoms [1]. If we could find such features in this study, it would be helpful for university students to live a mentally and physically healthy campus life.…”
Section: Introductionmentioning
confidence: 52%
“…This consistence with the results of previous studies which find that the high score immature level of defense mechanism. [8,22] After implementing the program, the findings illustrated that there statistically significant difference between pre to post program for intervention group through using neurotic defense mechanisms, which the intervention group indicated higher scores than the control group with statistically significant difference. Thus, training program improved using students' neurotic defensive mechanisms.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, gender differences are found in those hormones and the number and subsets of leucocytes and male are basically more SN dominance [23]. As for gender difference in psychological field, Shichiri K reported in detail [14] [24].…”
Section: Gender Differencementioning
confidence: 99%